2013
DOI: 10.1371/journal.pone.0071191
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Disease Candidate Proteins in Cardiomyopathy-Specific Protein-Protein Interaction Networks Based on “Guilt by Association” Analysis

Abstract: The cardiomyopathies are a group of heart muscle diseases which can be inherited (familial). Identifying potential disease-related proteins is important to understand mechanisms of cardiomyopathies. Experimental identification of cardiomyophthies is costly and labour-intensive. In contrast, bioinformatics approach has a competitive advantage over experimental method. Based on “guilt by association” analysis, we prioritized candidate proteins involving in human cardiomyopathies. We first built weighted human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Thus, a TF sequence variant becomes linked to user-entered disease phenotype keywords in a process known as ‘guilt by association’ (62, 65). Importantly, this line of analysis symmetrically applies to cases in which a variant occurs in a candidate target gene, whereas the phenotype is linked to a TF gene.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a TF sequence variant becomes linked to user-entered disease phenotype keywords in a process known as ‘guilt by association’ (62, 65). Importantly, this line of analysis symmetrically applies to cases in which a variant occurs in a candidate target gene, whereas the phenotype is linked to a TF gene.…”
Section: Resultsmentioning
confidence: 99%
“…PPI networks provide information on the function of important protein(s) based on the guilt-by-association principle, i.e. highly interconnected proteins potentially share functional property and might be part of the same biochemical pathway(s) [ 95 ]. PPI networks can be built manually [ 96 ], allowing the merging of PPI data obtained from different sources: this approach is time-consuming, but allows the handling of the raw PPIs through custom filters and to create multi-layered networks.…”
Section: The Proteome and Proteinomicsmentioning
confidence: 99%
“…This finding was further supported by our computational analysis where we applied a systems biology approach focused on the tau protein interactome on the basis of the guilt by association principle (i.e. the unknown function of protein A can be inferred via the known function of protein B if A and B interact) (44). Functional annotation analysis of the in silico model of tau’s interactome showed that over 1/3 rd of tau interactors was directly involved in functions such as DNA damage, response to radiation stressors, DNA damage checkpoint, repair and cell death, cell cycle checkpoints and chromatin maintenance, processes that are arguably associated with cancer; this is cross-supportive with previous computational work when considering tau’s co-expression or PPI-networks analyses in FTLD (28,45).…”
Section: Discussionmentioning
confidence: 58%